2014
DOI: 10.1128/jcm.00100-14
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory Reproducibility and Proficiency Testing within the Human Papillomavirus Cervical Cancer Screening Program in Catalonia, Spain

Abstract: P ersistent infection with oncogenic human papillomaviruses (HPVs) is necessary for the development of invasive cervical cancer (CC) (1-3). CC screening based on cervical cytology has been instrumental in decreasing the incidence and mortality associated with CC in those countries with high screening coverage rates (4). However, the infectious etiology of this disease leads to the suggestion that the detection of the DNA of HPVs responsible for cellular transformation might provide a strong predictive marker f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…A positive result was considered if attained or exceeded the FDA-approved threshold of 1.0 relative light unit (RLU/CO). All HPV reference laboratories were part of a quality control with kappa values over 90% [25].…”
Section: Screening Tests and Gold Standard Testmentioning
confidence: 99%
“…A positive result was considered if attained or exceeded the FDA-approved threshold of 1.0 relative light unit (RLU/CO). All HPV reference laboratories were part of a quality control with kappa values over 90% [25].…”
Section: Screening Tests and Gold Standard Testmentioning
confidence: 99%
“…Further, the results of the proficiency testing assessment among laboratories for the HPV test showed that the HC2 assay has a high interlaboratory concordance [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Every year, 20 samples stratified by different value categories were retested in a different laboratory from the original one. Concordance analyses were performed through the Kappa statistics and by linear regression as detailed elsewhere [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations